The Effect of Mind Mapping Technique on the Eleventh Grade of Senior High School Students’ Descriptive Writing Achievement. - Like W. Wibowo (Widya Mandala Surabaya Catholic University, 2008)
In this study, the writer used a quasi experimental nonequivalent-groups pretest-post test design. The subjects of this study were the eleventh grade students of Senior High School. The writer took two classes as the sample of this experiment. The experimental group was taught using mind mapping and another was taught using semi-controlled writing. Then, the writer gave a pre test, post test and even questionnaire to the two groups. The pre test was intended to measure the students’ descriptive writing ability in some criteria before the treatments. The treatments were given three times ninety minutes each. The writer used post test as one of the instruments to see the students’ descriptive writing achievement in some criteria and questionnaire to know the students’ response of two techniques used. After that, the writer evaluated the students’ pre and post test of the two groups by using the analytic scoring technique, ESL Composition Profile. Their means differences were analyzed using the t-test formula to see whether there is a different significant effect of students’ writing achievement in their content, organization, vocabulary, and language use criteria. Basing on the calculation of t-test, the writer found the t observation of both groups. The t observation of content, organization, vocabulary, and language use criteria of the two groups were 1.88, 1.7, 11.49, and 1.22 while the t-table of both was 1.671. In conclusion, the result of the calculation of the students’ test in both experimental and control group shows that mind mapping yields a significant effect of writing achievement in content, organization and vocabulary criteria and gets good response in teaching writing with enjoyable and interesting atmosphere.